The ways of implementing interactive methods in the educational process of students of higher educational institutions - Y.V. Vaskov; I.E. Sizonenko (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : theoretical basis and practical implementation of interactive methods in the educational process of higher education institutions. Material : еhe study involved 50 students of the Kharkiv humanitarian-pedagogical Academy. Results : ыhowing the possibility of introducing interactive teaching method "Joint project." The theoretical study and practical implementation of the method is the process of inclusion of all students in the joint study group (in the form of small groups) work on mastering the content of teaching material. Also, the presentation of educational options to solve their own problems, discussion of the results of joint activities, making optimal decisions. Conclusions : еhe development of theoretical foundations and practical implementation of an interactive method improved the quality of the educational process of students. This is reflected in the involvement of all students in active joint work on learning. Also provide an opportunity for each student to express their own opinions on those tasks. This increased level of theoretical knowledge of each student.